The slope-intercept form of a linear equation is given by y = mx + b, where m is the slope of the line and b is the y-intercept.
In the given equations, we can identify the slope and y-intercept for each equation:
1. 3x - y = 4
Rearranging the equation to slope-intercept form:
-y = -3x + 4
y = 3x - 4
Here, the slope (m) is 3 and the y-intercept (b) is -4.
2. y = -3x - 4
This equation is already in slope-intercept form, where the slope (m) is -3 and the y-intercept (b) is -4.
3. y = 3x - 4
Here, the slope (m) is 3 and the y-intercept (b) is -4.
4. y = 3x + 4
Here, the slope (m) is 3 and the y-intercept (b) is 4.
using the graph derive the equation of the line in the slope-intercept from
3x - y = 4
y = -3x - 4
y = 3x - 4
y = 3x + 4
1 answer